Bacteria-mediated anti-cancer therapy - Bhave, Madhura Satish (2019)
Traditional cancer treatments like chemotherapy and radiation therapy continue to have limited efficacy due to phenomena like tumor hypoxia and multi-drug resistance. Bacterial cancer therapy has the potential to overcome these problems, using anaerobic spores of bacteria such as the proteolytic Clostridium sporogenes. However, the use of spores or live bacteria comes with the risks of toxicity, infection and tumor recurrence. This thesis is motivated by the research question, “How can bacterial therapy be made safer while retaining the natural anti-cancer properties of bacteria?”. To address this question, heat-inactivated bacteria (IB) and conditioned media (CM) with the secreted products of C. sporogenes were generated to minimize the safety and efficacy risks of live bacteria. These derivatives of C. sporogenes, which are cannot replicate or metabolise, were tested for their anti-cancer properties for the first time. It was hypothesized that these non-viable derivatives of C. sporogenes can exert a direct anti-cancer effect and elicit an immune response against tumors. The direct anti-cancer effect of IB and CM was investigated using a range of human cancer cells of various tissue origin: colorectal (HCT116), breast (MCF7), renal (A498), hepatic (HepG2), bladder (RT4) and melanoma (G361). These in vitro studies were conducted on 2-Dimensional (2D) monolayer and 3-Dimensional (3D) spheroid culture models. The results showed that IB and CM have a selective anti-cancer effect on the different cell lines. Colorectal cancer cells were found to be the susceptible to IB and CM treatment in both in vitro models, resulting in significant decreases in cell proliferation and spheroid size. Subsequent studies were conducted on colorectal cancer cell lines HCT116 (human) and CT26 (murine) to understand the nature of IB- and CM- mediated inhibition. The inhibition of HCT116 and CT26 cells when kept in cell culture-conditions showed that the anti-cancer efficacy of IB and CM was hypoxia-independent. This would minimize the risk of tumor recurrence associated with hypoxia-dependent spores and live anaerobic bacteria. Scanning electron microscopy imaging showed that the IB adherent to the surface of cancer cells and restricted-culture studies proved that physical contact between IB and cancer cells was crucial for inhibition. IB was found to mediate necrosis in colorectal cancer cells. On the other hand, CM was found to mediate apoptosis in the cancer cells. To understanding the mechanism of CM-mediated cancer inhibition, the active component of CM was examined. Size fractionation of CM showed that the fraction of size smaller than 3 kDa in molecular weight retained the inhibitive of CM. The findings suggested that IB and CM have intrinsically different mechanisms of cancer inhibition. After successfully inhibiting the growth of CT26 and HCT116 colorectal cancer cells in vitro, the efficacy of IB and CM was tested in mouse models of colorectal tumors. Sub-cutaneous tumors of CT26 and HCT116 cells were established in BALB/cARC and athymic BALB/c-Foxn1nu/ARC (nude) mice, respectively. IB and CM were administered through intra-tumoral injections over a period of 12 days, during which the tumor volume was measured. CM had limited efficacy in decreasing the tumor-burden of the mice and did not elicit an immune response. However, IB significantly inhibited the growth of the tumors and improved the survival rate of immunocompetent CT26 tumor-bearing mice. Histological analysis showed that IB increased the necrotic area in HCT116 tumors. Immunohistochemical analysis of the tumor samples showed that IB elicited an immune response against the tumor cells. Notably, when the IB-treated mice were subsequently re-challenged with CT26 cells, the immune mediated-response prevented the establishment of a second tumor in the mice. Taken together, the results show in vivo efficacy of the non-viable derivatives of C. sporogenes. In summary, the work of this thesis demonstrates the potential of IB and CM of C. sporogenes as anti-cancer agents which retain the natural anti-cancer properties of the bacteria and advantages over conventional therapy, while minimizing the safety risks.